Clinical efficacy and safety of individualized pembrolizumab administration based on pharmacokinetic in advanced non-small cell lung cancer: A prospective exploratory clinical trial. (April 2023) - Wang, Na; Zheng, Lie; Li, Meichen; Hou, Xue; Zhang, Baishen; Chen, Jing; Li, Su; Chen, Likun
Highlights: Whether PK-guided pembrolizumab in advanced NSCLC is a rational therapeutic strategy. Pembrolizumab administration under PK-guided was an alternative rational strategy. Personalized optimal treatment of pembrolizumab can reduce economic toxicity. Abstract: Introduction: Pembrolizumab is recommended with a fixed dose of 200 mg 3-weekly. We performed this study to explore the clinical efficacy and safety of pharmacokinetic (PK)-guided pembrolizumab administration in advanced non-small cell lung cancer (NSCLC). Methods: In this prospective exploratory study, we enrolled advanced NSCLC patients in Sun Yat-Sen University Cancer Center. Eligible patients received pembrolizumab 200 mg 3-weekly with or without chemotherapy for four cycles, then for patients without progressive disease (PD), pembrolizumab was administrated in new dose-intervals according to steady state plasma-concentration (Css) of pembrolizumab until PD. We set the effective concentration (Ce) at 15 μg/ml and new dose-intervals (T) was calculated according to Css of pembrolizumab using following equation: Css × 21D = Ce (15 μg/ml) × T. Primary endpoint was the progression-free survival (PFS), secondary endpoints were objective response rate (ORR) and safety. Besides, advanced NSCLC patients received pembrolizumab 200 mg 3-weekly and more than four cycles in our center were defined as the history-controlled cohort. Patients with Css of pembrolizumab underwent genetic polymorphism analysis of variable number of tandem repeats (VNTR) region in neonatal Fc receptor (FcRn). The study was registered at ClinicalTrials.gov, NCT05226728. Results: A total 33 patients received pembrolizumab in new adjusted dose-intervals. The Css of pembrolizumab ranged from 11.01 to 61.21 μg/ml, 30 patients need prolonged intervals (22-80d) and 3 shortened intervals (15–20 d). In PK-guided cohort, the median PFS was 15.1 months and ORR 57.6 %, whereas in history-controlled cohort was 7.7 months and ORR 48.2 %. The immune-related adverse events were 15.2 % and 17.9 % between two cohort. The VNTR3/VNTR3 genotype of FcRn had significantly higher Css of pembrolizumab than VNTR2/VNTR3 (p = 0.005). Conclusions: PK-guided pembrolizumab administration showed promising clinical efficacy and manageable toxicity. Meanwhile less frequent dosing of pembrolizumab by PK-guided could reduce financial toxicity potentially. This provided an alternative rational therapeutic strategy of pembrolizumab in advanced NSCLC.